2008
DOI: 10.1200/jco.2008.17.1496
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Staging of Large Primary Breast Cancer With [18F]Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Compared With Conventional Imaging Procedures

Abstract: PET/CT underestimates locoregional lymph node staging in large primary breast cancer patients. PET/CT is a valuable tool to discard unsuspected extra-axillary lymph nodes and distant metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
261
3
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 264 publications
(288 citation statements)
references
References 27 publications
17
261
3
6
Order By: Relevance
“…Also, falsepositives resulting from muscular and brown fat uptake are avoided. In a prospective study of 60 breast tumours larger than 3 cm, PET/CT revealed unsuspected infraclavicular node involvement (N3a) in two patients, supraclavicular node involvement (N3c) in one patient and contralateral axillary involvement (M1) in one patient [9]. Differentiating level III axillary lymph nodes (infraclavicular lymph nodes located superomedially to the pectoralis minor muscle) is important since axillary clearance usually addresses Berg level I and II nodes only.…”
Section: Axillary and Extra-axillary Lymph Node Stagingmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, falsepositives resulting from muscular and brown fat uptake are avoided. In a prospective study of 60 breast tumours larger than 3 cm, PET/CT revealed unsuspected infraclavicular node involvement (N3a) in two patients, supraclavicular node involvement (N3c) in one patient and contralateral axillary involvement (M1) in one patient [9]. Differentiating level III axillary lymph nodes (infraclavicular lymph nodes located superomedially to the pectoralis minor muscle) is important since axillary clearance usually addresses Berg level I and II nodes only.…”
Section: Axillary and Extra-axillary Lymph Node Stagingmentioning
confidence: 99%
“…Depicting lymph node involvement in levels or basins other than those addressed by routine ALND may have major impact on treatment strategies. Many studies suggest that FDG PET performs better than conventional imaging in depicting involvement in high-level axillary (Berg level III) as well as in supraclavicular and internal mammary lymph nodes [8,9,[13][14][15]. PET/CT is particularly appealing compared to PET alone as it provides the precise location of involved nodes [7][8][9].…”
Section: Axillary and Extra-axillary Lymph Node Stagingmentioning
confidence: 99%
See 3 more Smart Citations